Characterization and Development of Ceramics with Inorganic Additives - Mirza Awais; Asif Mansoor; Imran Shah; Murtaza Hussain; Muhammad Asif (Inventions)
Date palm tree (DPT) and pine tree (PT) needles in forests form a combustible mat, posing fire risks during summer in Pakistan that damage vegetation, wildlife habitats, and biodiversity and impact local livelihoods. In this article, sintered ceramic specimens were prepared at different weight concentrations (DPT5, DPT10, DPT20, and DPT 30 and PT5, PT10, PT20, and PT30) of date palm tree leaf ash and pine tree needle ash as secondary additives in ceramic manufacturing along with primary material kaolinite (China clay). Raw materials composition was analyzed using X-ray diffraction (XRD), taking loss on ignition, water absorption, bulk density, saturated surface dry density (SSD), weight per unit area, and thermal cycling as measurement indexes. The result indicates that loss on ignition increases while increasing the quantity of secondary additives and the maximum increase for DPT30 was 19.6% and for PT30, it was 22.1%. As the secondary additives increase, the water absorption rate also increases and the maximum increase for DPT30 and PT30 is 4.5%. Meanwhile, with the increase in secondary additives, the density decreased; for DPT 30, it was 1457.7 kg/m3 and for PT30, it was 1829.8 kg/m3. Thermal performance was investigated by heating and cooling cycles. It was observed that thermal performances increase with the increase in secondary additives. The results reveal this novel approach has the potential to form a ceramic and good properties can be achieved. The prepared specimens have the potential to be used in the fields of electronics, aerospace, construction, and building engineering, alleviating environmental strain, curbing the exhaustion of China clay reserves, and most importantly, lowering the risk of forest fires in Pakistan.